Prediction of the Students\' Social Well-being: The Role of Psychological Hardiness and Emotions (Positive and Negative Emotion) - Razie Dehlani; Ali Hossein Khani; Omid Mirzaei Fandokht; Zeynab Moradi Sirich (Mazandaran University of Medical Sciences, 2021)
Introduction and purpose: The social well-being of the students as an influential group, who face different experiences in society, university, and family, is affected by various factors. Therefore, this study aimed to investigate the role of psychological hardiness components and emotions (positive and negative) in predicting the students' social well-being. Methods: This study was conducted based on a descriptive-correlational research method. The statistical population included all students at the School of Nursing and Midwifery in Ghaen, Iran, during the academic year 2020-21. The samples (n=180) were selected using the convenience sampling method, as well as Gajresi and Morgan table. They were then asked to answer the questionnaires online. The data were collected using the Psychological Hardiness Scale (Kiamarsi et al., 1998), Positive and Negative Affect Schedule (Watson et al., 1988), as well as the Social Well-being Subscale (Keyes and Magyar-Moe, 2003). The obtained data were analyzed in SPSS software (version 25) through the Pearson correlation test and multiple regressions simultaneously. Results: The results showed a direct correlation between positive emotion and psychological hardiness with social well-being; however, there was an inverse and significant association between negative emotion and social well-being (P<0.01). Moreover, the results of the regression revealed that emotions and psychological hardiness explained 40% of the variance in social well-being. Conclusion: The results emphasize the development of psychological hardiness and the promotion of positive emotion in order to increase the social well-being of students during Coronavirus disease-2019 pandemic.